2017
DOI: 10.3389/fpls.2017.00721
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Leaf Water Content by Visible and Near-Infrared Spectrometry and Multivariate Calibration in Miscanthus

Abstract: Leaf water content is one of the most common physiological parameters limiting efficiency of photosynthesis and biomass productivity in plants including Miscanthus. Therefore, it is of great significance to determine or predict the water content quickly and non-destructively. In this study, we explored the relationship between leaf water content and diffuse reflectance spectra in Miscanthus. Three multivariate calibrations including partial least squares (PLS), least squares support vector machine regression (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 29 publications
1
57
0
Order By: Relevance
“…Ten fresh leaves were weighed, and oven dried at 105 • C for 0.5 h and at 70 • C for 72 h or until reaching a constant weight, and then dry weight of leaves was recorded. The leaf water content (%) was calculated using the following Equation (Jin et al, 2017).…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Ten fresh leaves were weighed, and oven dried at 105 • C for 0.5 h and at 70 • C for 72 h or until reaching a constant weight, and then dry weight of leaves was recorded. The leaf water content (%) was calculated using the following Equation (Jin et al, 2017).…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…W had also been reported to be positively correlated with leaf mesophyll thickness (Garnier and Laurent 1994) and nitrogen content (Roderick et al 1999b), and had also been reported to be strongly associated with maximum photosynthetic efficiency and relative growth rate (Garnier and Laurent 1994, Smith et al 1997, Lusk and Reich 2000. W is also an indicator of tolerance to water deficit because low water content restricts transpiration and causes closure of stomata (Jin et al 2017). In the leaf, W is mainly represented by mesophyll tissue and epidermis (Roderick et al 1999a, Westoby et al 2002.…”
Section: Introductionmentioning
confidence: 98%
“…where y is the actual LNC obtained by the experiment of laboratory measurement, y is the mean value of the actual LNC, andŷ is the predicted LNC obtained by multiple regression analysis using the least square method [33][34][35][36]. The predicted leaf nitrogen concentrations were validated by comparison with the actual leaf nitrogen concentrations.…”
Section: Resultsmentioning
confidence: 99%